The Influence Of Community-Based Ecotourism On Changing Social And Economic Conditions In Osi Island Village West part of seram district - Hardin Lamani; JF Sopamena; NF Wenno (Cita konsultindo, 2024)
Indonesia has the potential for natural beauty and cultural riches that are of high value in the ecotourism industry market. This natural potential can be in the form of biological natural resources and their ecosystems, diversity of flora, fauna and natural phenomena with the beauty of unspoiled views. Research Location The location of this research is Pulau Osi Hamlet, West Seram District, West Seram Regency. The research will be carried out in November - December 2022. Based on the results and discussion, the conclusion is that the economy is any additional economic capability received by society which can be used for consumption or to increase people's income. Community education can be carried out by providing adequate access to education for the community through scholarships, training and developing human resource potential.